X+6=3x-2(x-3)

Simple and best practice solution for X+6=3x-2(x-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for X+6=3x-2(x-3) equation:


Simplifying
X + 6 = 3x + -2(x + -3)

Reorder the terms:
6 + X = 3x + -2(x + -3)

Reorder the terms:
6 + X = 3x + -2(-3 + x)
6 + X = 3x + (-3 * -2 + x * -2)
6 + X = 3x + (6 + -2x)

Reorder the terms:
6 + X = 6 + 3x + -2x

Combine like terms: 3x + -2x = 1x
6 + X = 6 + 1x

Add '-6' to each side of the equation.
6 + -6 + X = 6 + -6 + 1x

Combine like terms: 6 + -6 = 0
0 + X = 6 + -6 + 1x
X = 6 + -6 + 1x

Combine like terms: 6 + -6 = 0
X = 0 + 1x
X = 1x

Solving
X = 1x

Solving for variable 'X'.

Move all terms containing X to the left, all other terms to the right.

Simplifying
X = 1x

See similar equations:

| 4x-6=-x+54 | | y=2lx-2l+7 | | f-27=4f | | -3x=19-4 | | .10(x-4)+.02x=.06x-.7 | | -12=3x-5x | | 8t^2-19t+11=0 | | -6x-6=3x-15 | | y=sqrt-9-2 | | 209=19*11+13n | | 3y^3-193=0 | | 6-8n=0 | | (X-3)(x+4)-30=0 | | 8x-5-2x+5=18+8x | | -6x+3=-45+2x | | 5+24=x+8 | | 3(y-10)+1=6(y-8) | | -4x+8=-2+x | | 5-5z=-3z | | x+3=-26+15 | | -8.2-1.7= | | 4x+2(14-x)=40 | | X=-0.142+-0.285(10.90) | | -10+x=-x+12 | | 23=b+s | | 5x(10)=81 | | N(10)+N(5)+N(0)+N(23)+N(10)= | | 15=51c-13 | | 35=-6t-7 | | -4x+5=5+7x | | (4n+13)8=6n | | 3a+3=5a-9 |

Equations solver categories